Teaching Literature Enhances Communication Skills – a Study with Special Emphasis on Poetry - Ilankumaran, M; Deepa, P (International Journal of Engineering and Technology, 2018)
The term communication is one of the most analyzed terms in the academic arena and it has been studied systematically since ancient times. Communication is an everyday social activity that is an essential and inherent component of every human being. It is a key to human development because the quality of the existence is linked directly to the quality of the communication. This article focuses on how literature in general and poetry in particular enhances the communication skills of the students. Every literary person knows about language and literature. However, they are most common to learn the vocabulary. Literature plays a key role in language classroom. It provides not only pleasure to readers but also builds experience and creates thinking ability. Moreover, literature has several literary forms such as prose, poetry, drama, novel, short stories, etc. Though there are several forms in literature, the most interesting genre is poetry. Poetry can be the works of great beauty due to its meter and rhyme scheme like the ebb and flow of an ocean. This really helps the student to show more involvement towards poetry. On the other hand, the students can try to know more vocabulary from the lines of the poems. Through different terms of poetry used in the classroom, the students get more benefits of knowing new terms and words.Â Â